2017
DOI: 10.1038/s41598-017-01918-7
|View full text |Cite
|
Sign up to set email alerts
|

TaPIMP2, a pathogen-induced MYB protein in wheat, contributes to host resistance to common root rot caused by Bipolaris sorokiniana

Abstract: MYB transcription factors (TFs) have been implicated in various biology processes in model plants. However, functions of the great majority of MYB TFs in wheat (Triticum aestivum L.) have not been characterized. The soil-borne fungal pathogens Bipolaris sorokiniana and Rhizoctonia cerealis are the causal agents of important destructive diseases of wheat. Here, the TaPIMP2 gene, encoding a pathogen-induced MYB protein in wheat, was isolated through comparative transcriptomic analysis, and its defensive role was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The tested genes included β-1,3-Glucanase , Defensin , Chitinase1 , Chitinase3 , and Chitinase4 , which have been shown to participate positively in wheat resistance responses to B. sorokiniana and R . cerealis [ 27 , 28 , 29 , 30 ]. Fifteen days after inoculation with B. sorokiniana , the transcriptional levels of β-1,3-Glucanase , Defensin , Chitinase3, and Chitinase4 ( Figure 8 A–D) were significantly decreased in TaCRR1 -silenced Yangmai 6 plants relative to the BSMV: GFP-infected Yangmai 6 plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested genes included β-1,3-Glucanase , Defensin , Chitinase1 , Chitinase3 , and Chitinase4 , which have been shown to participate positively in wheat resistance responses to B. sorokiniana and R . cerealis [ 27 , 28 , 29 , 30 ]. Fifteen days after inoculation with B. sorokiniana , the transcriptional levels of β-1,3-Glucanase , Defensin , Chitinase3, and Chitinase4 ( Figure 8 A–D) were significantly decreased in TaCRR1 -silenced Yangmai 6 plants relative to the BSMV: GFP-infected Yangmai 6 plants.…”
Section: Resultsmentioning
confidence: 99%
“…Inoculated plants were grown at ~80% relative humidity. The disease symptoms of these plants were observed at 15 dpi, and ITs and sharp eyespot/common root rot disease indexes of these plants were scored at 35 dpi [ 6 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Western blotting analysis using an antibody against MYC tag revealed that introduced MYC‐ Ta ERFVII.1 fusion protein constitutively accumulated in these three transgenic wheat lines under both standard conditions and waterlogging conditions (Figure c). The ddPCR has been proven to be a reliable and accurate method in estimation of transgene copy number in wheat (Collier et al, ; Wei et al, ). We further estimated the copy number of introduced TaERFVII.1 in three transgenic wheat lines using ddPCR with the wheat PINb (PUROINDOLINE‐b) gene as a single copy reference gene (Collier et al, ; Li et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It can infect the roots and basal stems at any time during the wheat growing season, and in turn can devastate the transport of tissues in stems of wheat and obstruct transportation of nutrition substances [3,6]. Common root rot, caused by the soil-borne fungus Bipolaris sorokiniana, is another important disease of wheat [7]. B. sorokiniana mainly infects the roots and stem bases of wheat plants.…”
Section: Introductionmentioning
confidence: 99%